The Southern Pine Beetle Dendroctonus frontalis (Coleoptera: Curculionidae: Scolytinae) - Demian F. Gomez; Jiri Hulcr (EDIS, 2019)
The southern pine beetle, Dendroctonus frontalis Zimmermann, is the most destructive insect pest of pine in the southern United States. This 8-page fact sheet written by Demian F. Gomez and Jiri Hulcr and published by the UF/IFAS Department of Entomology and Nematology describes the beetle and includes advice on how to monitor for them and strategies for their prevention and control. http://edis.ifas.ufl.edu/in333